2020
DOI: 10.1108/ccij-01-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Distrust in corporate communications: does it matter?

Abstract: PurposeThis study provides much needed empirical data to conceptualise organisational distrust in communications' scholarship. A limited understanding of distrust has implications for corporate communication scholars and practitioners as, ultimately, efforts to rebuild trust and reduce distrust in organisations and corporations may be hindered if we do not truly understand the complexity and nature of the concepts we are trying to repair.Design/methodology/approachA repeated single-criterion card-sort method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Overall, this research joins recent studies that have found responsibility and irresponsibility perceptions to be separate constructs (Clark et al, 2022;Swaen et al, 2021). To help advance our understanding of consumers' responses to these perceptions, we have treated trust and distrust as two distinct variables following recent communication literature (Tyquin et al, 2021) and previous management (Lewicki et al, 1998) and retail research (Cho, 2006). Our study demonstrates that splitting global trust into two constructs can be useful in explaining consumers' responses to their responsibility perceptions, particularly, negative ones (i.e.…”
Section: Theoretical Implicationsmentioning
confidence: 58%
See 1 more Smart Citation
“…Overall, this research joins recent studies that have found responsibility and irresponsibility perceptions to be separate constructs (Clark et al, 2022;Swaen et al, 2021). To help advance our understanding of consumers' responses to these perceptions, we have treated trust and distrust as two distinct variables following recent communication literature (Tyquin et al, 2021) and previous management (Lewicki et al, 1998) and retail research (Cho, 2006). Our study demonstrates that splitting global trust into two constructs can be useful in explaining consumers' responses to their responsibility perceptions, particularly, negative ones (i.e.…”
Section: Theoretical Implicationsmentioning
confidence: 58%
“…, 2021). To help advance our understanding of consumers' responses to these perceptions, we have treated trust and distrust as two distinct variables following recent communication literature (Tyquin et al. , 2021) and previous management (Lewicki et al.…”
Section: Discussionmentioning
confidence: 99%